Patient Experience and Virtual Reality: The Use of an MRI Exam Simulator - Jaqueline da Silva; Marcus de Souza; Mônica dos Santos; Milena Melo; Lorena Almeida; Alayde Silva; Êmilly Vieira; Alessandra Pontes; Jandson Soares (Patient Experience Journal)
Magnetic resonance (MR) imaging is a safe diagnostic method of high accuracy detection and characterization of various pathological conditions. However, due to the very closed aspect of the apparatus, the high sound amplitude emitted and the need to remain motionless for a significant time, some patients experience discomfort and high levels of anxiety, compromising time and image quality management that can impair the clinical outcome of the patient or even give up the performance of this procedure. Therefore, this study aimed to validate, with patients, the use of Virtual Reality (VR) as a humanized practice of exposure to magnetic resonance imaging, to reduce the discomfort often present in the procedure. For this purpose, we used a cross-sectional method of quantitative-qualitative approach, incorporating purposeful sampling and semi-structured interviews of evaluative nature with 303 patients from two health institutions located in the state of Alagoas, Brazil, in which patients immersed in VR before the examination. As a result, exposure to VR led 98.9% of patients to feel more prepared and confident to perform the examination. There was no significant correlation between age, previous contact with technology and gender with the effectiveness of the intervention. However, there was a significant correlation between the form of approach, the quality of information and the level of feeling of relaxation of the patient. Thus, these results highlight the positive impact of VR on the patient's experience in performing the MRI examination and the variety of audiences that can enjoy the benefits that this technology provides.